Modernization System Taxation in the Midst of the Digital Economy Wave : A Study Literature - Nugroho Dwi Prihandoko; Gita Astyka Rahmanda (Universitas Muhammadiyah Makassar, 2024)
The growth of the digital economy in Indonesia, driven by technological developments and widespread internet access, has changed the transaction landscape from traditional to digital methods. In 2016, the value of online transactions reached IDR 75 trillion and is expected to increase to IDR 144 trillion in the next few years, with the e-commerce sector growing rapidly and expected to reach IDR 600 trillion in 2024. This change has given rise to new challenges in the taxation system, especially in addressing cross-border taxes and tax complexity on digital platforms. This article uses a literature review approach to evaluate the evolution of the tax collection system from traditional methods to a digital system. This study identifies that the paper-based taxation system, with manual processes and prone to errors, has been replaced by increased efficiency and transparency of digital technology. The implementation of e-filing and e-payment systems, as well as advanced technologies such as big data, artificial intelligence (AI), and blockchain, have improved tax administration. These technologies facilitate more data collection and analysis, improve detection of non-compliance, and provide a secure system for digital transactions. However, this evolution also brings challenges such as cross-border taxes and complex digital transaction management. The definition of permanent establishment (PE) should be expanded to include digital entities, and new taxes such as equalization levies are needed to address cross-border tax issues. Responsive and innovative tax reforms are essential to address these challenges and ensure sustainable income taxation in the digital age. International collaboration and global harmonization of tax policies are key to addressing tax issues arising from the digital economy.